2012
DOI: 10.1111/j.1365-3040.2012.02480.x
|View full text |Cite
|
Sign up to set email alerts
|

Wheat WRKY genes TaWRKY2 and TaWRKY19 regulate abiotic stress tolerance in transgenic Arabidopsis plants

Abstract: WRKY-type transcription factors are involved in multiple aspects of plant growth, development and stress response. WRKY genes have been found to be responsive to abiotic stresses; however, their roles in abiotic stress tolerance are largely unknown especially in crops. Here, we identified stress-responsive WRKY genes from wheat (Triticum aestivum L.) and studied their functions in stress tolerance. Forty-three putative TaWRKY genes were identified and two multiple stress-induced genes, TaWRKY2 and TaWRKY19, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
271
3
9

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 407 publications
(299 citation statements)
references
References 78 publications
(157 reference statements)
16
271
3
9
Order By: Relevance
“…One study showed that co-regulated networks involving WRKY genes were important in regulating the responses of pak-choi to a variety of abiotic stresses [27]. Wheat TaWRKY19 regulates the expression of DREB2A, which encodes a key transcription factor that controls the expression of drought-related genes [56]. Therefore, the regulatory roles of WRKY genes in response to abiotic stresses are complex and further studies are required to understand their functions in sesame.…”
Section: Functional Divergence and Segmental Duplication Of Wrky Genesmentioning
confidence: 99%
“…One study showed that co-regulated networks involving WRKY genes were important in regulating the responses of pak-choi to a variety of abiotic stresses [27]. Wheat TaWRKY19 regulates the expression of DREB2A, which encodes a key transcription factor that controls the expression of drought-related genes [56]. Therefore, the regulatory roles of WRKY genes in response to abiotic stresses are complex and further studies are required to understand their functions in sesame.…”
Section: Functional Divergence and Segmental Duplication Of Wrky Genesmentioning
confidence: 99%
“…Multiple genes encoding stress-related transcription factors were identified within the overlap of putative ERF6 target genes and genes transcriptionally induced within 24 h after osmotic stress exposure (Skirycz et al, 2011a). To further uncover the link between ERF6 and this stress-related transcription factor network, we chose three representative genes, STZ, WRKY33, and MYB51, as these were previously shown to have a role in biotic and abiotic stress signaling (Sakamoto et al, 2000(Sakamoto et al, , 2004Gigolashvili et al, 2007;Jiang and Deyholos, 2009;Birkenbihl et al, 2012;Li et al, 2012;Niu et al, 2012). Additional quantitative PCR analysis confirmed the induction of these genes within 2 h after DEX-mediated ERF6 activation using the ERF6 IOE -S (Fig.…”
Section: Erf6 Activates a Plethora Of Stress-responsive Genesmentioning
confidence: 99%
“…The transcript pre_comp28074_c0_seq1, showed sequence identity (identity: 68%, E value: 2e-14) to a WRKY in Triticum aestivum whose overexpression improves stress tolerance in transgenic Arabidopsis plants through regulation of downstream genes (Niu et al 2012) as well as sequence identity (identity: 86%, E value: 2e-11) with WRKY genes in Brassica napus responding to fungal pathogens (Yang et al 2009). …”
Section: Discussionmentioning
confidence: 99%